Aktualisasi Patronasi untuk Membangun Perilaku Peduli Lingkungan pada Kalangan Siswa Sekolah Adiwiyata di Padelegan Pamekasan - Asih, Eka Nurrahema Ning; Rizqiyeh, St.; Sofiya, Lely; Widiyawati, Devita; Setiawati, Sulastiana; Nuzula, Nike Ika; Pratiwi, Wiwit Sri Werdi; Kartika, Ary Giri Dwi; Wicaksono, Ashari; Siswanto, Aries Dwi; Efendy, Makhfud (Pakis Journal Institute, 2025)
Padelegan Village is a coastal village that has a high risk of experiencing physiological stress in the form of pollution produced by domestic waste and industrial waste. This community service activity aims to foster an attitude of caring for the environment, especially character building in Padelegan 1 Elementary School students from an early age. This activity was carried out using three activity programs, namely socializing environmental awareness, reforestation practices through planting green beans and family medicinal plants (toga), education on types of waste, and making rubbish bins using used goods (gallons). The results of the activity showed that as many as 30 students representing 10 students each from classes IV, V, and VI showed that all students were interested in applying and re-practicing the activities that had been carried out. This shows that the entire program that has been carried out and the objectives of the program that have been implemented have succeeded in fostering an attitude of caring for the environment from an early age.